Understanding English grammar : a linguistic approach - Wardhaugh, Ronald (Oxford, U.K. : Blackwell, 1995)
Preliminaries. Word classes. Constituents and phrases. Basic clauses. Coordination and embedding. Clausal variation. Underlying relationships. Rules and principles. Sounds and systems. Phonetic realization. Word formation. Words and sounds. Sounds in context.
Keywords: English language; Grammar; English language -- Grammar